Activation of Dopamine 4 Receptor Subtype Enhances Gamma Oscillations in Hippocampal Slices of Aged Mice - Wang, Yuan; Jin, Yi-Kai; Guo, Tie-Cheng; Li, Zhen-Rong; Feng, Bing-Yan; Han, Jin-Hong; Vreugdenhil, Martin; Lu, Cheng-Biao (Frontiers in Aging Neuroscience, 2022)
Aim Neural network oscillation at gamma frequency band (γ oscillation, 30–80 Hz) is synchronized synaptic potentials important for higher brain processes and altered in normal aging. Recent studies indicate that activation of dopamine 4 receptor (DR4) enhanced hippocampal γ oscillation of young mice and fully recovered the impaired hippocampal synaptic plasticity of aged mice, we determined whether this receptor is involved in aging-related modulation of hippocampal γ oscillation. Methods We recorded γ oscillations in the hippocampal CA3 region from young and aged C57bl6 mice and investigated the effects of dopamine and the selective dopamine receptor (DR) agonists on γ oscillation. Results We first found that γ oscillation power (γ power) was reduced in aged mice compared to young mice, which was restored by exogenous application of dopamine (DA). Second, the selective agonists for different D1- and D2-type dopamine receptors increased γ power in young mice but had little or small effect in aged mice. Third, the D4 receptor (D4R) agonist PD168077 caused a large increase of γ power in aged mice but a small increase in young mice, and its effect is blocked by the highly specific D4R antagonist L-745,870 or largely reduced by a NMDAR antagonist. Fourth, D3R agonist had no effect on γ power of either young or aged mice. Conclusion This study reveals DR subtype-mediated hippocampal γ oscillations is aging-related and DR4 activation restores the impaired γ oscillations in aged brain, and suggests that D4R is the potential target for the improvement of cognitive deficits related to the aging and aging-related diseases.